Role of Bunyamwera Orthobunyavirus NSs protein in infection of mosquito cells. - Agnieszka M Szemiel; Anna-Bella Failloux; Richard M Elliott (Public Library of Science (PLoS), 2012)
Bunyamwera orthobunyavirus is both the prototype and study model of the Bunyaviridae family. The viral NSs protein seems to contribute to the different outcomes of infection in mammalian and mosquito cell lines. However, only limited information is available on the growth of Bunyamwera virus in cultured mosquito cells other than the Aedes albopictus C6/36 line.To determine potential functions of the NSs protein in mosquito cells, replication of wild-type virus and a recombinant NSs deletion mutant was compared in Ae. albopictus C6/36, C7-10 and U4.4 cells, and in Ae. aegypti Ae cells by monitoring N protein production and virus yields at various times post infection. Both viruses established persistent infections, with the exception of NSs deletion mutant in U4.4 cells. The NSs protein was nonessential for growth in C6/36 and C7-10 cells, but was important for productive replication in U4.4 and Ae cells. Fluorescence microscopy studies using recombinant viruses expressing green fluorescent protein allowed observation of three stages of infection, early, acute and late, during which infected cells underwent morphological changes. In the absence of NSs, these changes were less pronounced. An RNAi response efficiently reduced virus replication in U4.4 cells transfected with virus specific dsRNA, but not in C6/36 or C7/10 cells. Lastly, Ae. aegypti mosquitoes were exposed to blood-meal containing either wild-type or NSs deletion virus, and at various times post-feeding, infection and disseminated infection rates were measured. Compared to wild-type virus, infection rates by the mutant virus were lower and more variable. If the NSs deletion virus was able to establish infection, it was detected in salivary glands at 6 days post-infection, 3 days later than wild-type virus.Bunyamwera virus NSs is required for efficient replication in certain mosquito cell lines and in Ae. aegypti mosquitoes.